2013
DOI: 10.1016/j.devcel.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-B, a Liver-Derived Plasma Protein Is Essential for Fertilization

Abstract: The zona pellucida (ZP) is a glycoprotein matrix surrounding mammalian oocytes. Upon fertilization, ZP hardening prevents sperm from binding to and penetrating the ZP. Here, we report that targeted gene deletion of the liver-derived plasma protein fetuin-B causes premature ZP hardening and, consequently, female infertility. Transplanting fetuin-B-deficient ovaries into wild-type recipients restores fertility, indicating that plasma fetuin-B is necessary and sufficient for fertilization. In vitro fertilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 39 publications
4
109
0
2
Order By: Relevance
“…Fetuin-B, also identified in our Sia-glycoprobe fractions, is another protein that regulates gamete fusion by restraining ovastacin protease activity, thereby maintaining ZP permeability until the first spermatozoon intrudes. After penetration, ovastacin overrides fetuin-B and initiates ZP hardening, thus preventing polyspermy (59).…”
Section: Discussionmentioning
confidence: 99%
“…Fetuin-B, also identified in our Sia-glycoprobe fractions, is another protein that regulates gamete fusion by restraining ovastacin protease activity, thereby maintaining ZP permeability until the first spermatozoon intrudes. After penetration, ovastacin overrides fetuin-B and initiates ZP hardening, thus preventing polyspermy (59).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that liver-originated circulating glycoprotein fetuin-B is essentially required to inhibit premature cleavage of ZP2 by inhibiting ovastacin (Dietzel et al, 2013).…”
Section: Box2 Potential Limitations Of Knockout Approachesmentioning
confidence: 99%
“…Descriptions of the protease web are difficult to assemble, as many proteases remain poorly studied and characterized. Likewise, many proteases have no described inhibitors and many predicted inhibitors have unknown protease targets and deorphanization examples are uncommon [41].…”
Section: Introductionmentioning
confidence: 99%